The Relationship Between Knowledge Level and Anxiety Level in Facing Menarche A Systematic Review of Cross Sectional Studies - Ningsih, Dwi Mulyati; Firmansyah, Mizwar Taufiq; Wawo, Balbina Antonelda M (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Menarche is the first menstruation in young women. In society, the issue of menstruation is still considered very taboo to discuss, so that young women lack good knowledge and attitudes about physical and psychological changes related to menarche problems. Usually young women will experience anxiety, worry, fear and anxiety when facing menarche. Articles searched via database from 2018-2022. Searches were obtained from the PUBMED and Google Scholar databases. The keywords used are